PERENCANAAN MANAJEMEN RANTAI PASOK DAUN MURBEI JENIS MORRUS ALBA L. UNTUK PRODUKSI TEH HERBAL - Ayudya Mahendaringratry (Teknik Kimia ITN Malang, 2024)
PKK RT II RW VI, Tlogomas Village, Malang City, is an iconic area, namely the mulberry area, where every house in this area has at least 2 mulberry plants of the Morrus Alba L type. So far, members of PKK Rdaun mulberry kareT II RW VI, Merjosari Village, Malang strives to produce products made from mulberry, both fruit and leaves and stems/ratings. One product that is expected to become a mainstay is herbal tea made from mulberry leaves because the content in mulberry leaves is very good for human health. The main obstacle that arises when applying supply chain management (SCM) is the supply of raw materials which are usually obtained from local residents, with the production process being dried in the sun and roasted, resulting in small amounts of raw materials shrinking by 60%. The supply of raw materials needs to be increased through land improvement and mulberry plant seeds. If raw materials are available in abundance, marketing will be wide open for mulberry leaf herbal tea products.